Changing trend of cataract blindness and visual outcomes after cataract surgery in adults aged 50 years and older: findings from the national eye surveys in Malaysia - Mohamad Aziz Salowi; Nor Fariza Ngah; Nyi Nyi Naing; Norasyikin Mustafa; Wan Radziah Wan Nawang; Siti Nurhuda Sharudin (BMJ Open Ophthalmology)
Background/aims Population surveys are required to measure the prevalence of cataract blindness in the community. We conducted simultaneous surveys in two regions in Malaysia in 2023 to estimate the prevalence of untreated cataract, measure the visual outcomes after cataract surgery and compare the results with the survey in 2014.Methods The surveys were done in Eastern and Sarawak administrative regions using the rapid assessment of avoidable blindness technique. It involved a multistage cluster sampling method, each cluster comprising 50 residents aged 50 years and older. The prevalence of cataract was determined through a visual acuity (VA) check and eye examination. The VA of those who had undergone cataract surgery was measured, and the findings were compared with the previous survey.Results A total of 9709 subjects, 50 years old and older, were examined (percentages of response were 94.5% and 96.2% for Eastern and Sarawak, respectively). Comparing the current to the previous survey in 2014, the prevalence of cataract at all levels of surgical thresholds (except unilateral VA <6/60 and <6/18 in the Eastern) was reduced. The percentages of cataract surgery visual outcomes with good VA (6/12) were improved, and those with poor VA (<6/60) were reduced in both regions.Conclusion There was a reduction in cataract prevalence and improved visual outcomes in both regions. These favourable results could be attributed to the surgical performance monitoring initiatives and the community cataract programme implemented soon after the survey in 2014.